2014
DOI: 10.1007/s12651-014-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

Employment adjustment in German firms

Abstract: Using a representative establishment data set for Germany, I show that, in line with the existing literature for several countries, firms' adjustment costs for employment are characterized by a fixed and convex functional form. Furthermore, they are asymmetric with dismissal costs exceeding hiring costs. An analysis of firms' adjustment in the period 1996-2010 also indicates that adjustment behavior has changed over time. Comparing the employment adjustment in the two observed business cycles comprising the ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 94 publications
1
7
0
Order By: Relevance
“…Similar evidence is presented for the production sector in Italy (Jaramillo et al ., ). Other studies confirm this outcome for Germany (Jung, ; Kölling, ), France (Abowd and Kramarz, ; Goux et al ., ; Kramarz and Michaud, ), and Norway (Nilsen et al ., ). On the other side, Pfann and Verspagen () for the Netherlands and Hamermesh (, 208) as well as Hamermesh and Pfann () for the US indicate larger hiring than firing costs.…”
Section: Theorical Considerations and Previous Studiessupporting
confidence: 54%
See 1 more Smart Citation
“…Similar evidence is presented for the production sector in Italy (Jaramillo et al ., ). Other studies confirm this outcome for Germany (Jung, ; Kölling, ), France (Abowd and Kramarz, ; Goux et al ., ; Kramarz and Michaud, ), and Norway (Nilsen et al ., ). On the other side, Pfann and Verspagen () for the Netherlands and Hamermesh (, 208) as well as Hamermesh and Pfann () for the US indicate larger hiring than firing costs.…”
Section: Theorical Considerations and Previous Studiessupporting
confidence: 54%
“…This supports the assumption that yearly data are overaggregated and the estimation of the time to adjust is upwardly inflated (cf. Jung, ). From the discussion, we therefore conclude that dynamic adjustment processes do not interfere with the results presented below, as they are usually completed within a year and the data do not allow estimating shorter periods.…”
Section: Theorical Considerations and Previous Studiesmentioning
confidence: 99%
“…As being covered by collective bargaining usually goes along with higher wages (for details, see Gürtzgen 2008, Addison et al 2014, this contributes to the backlog in wages found in eastern Germany. What is more, among those establishments covered by collective agreements the probability of paying wages above the level stipulated in the agreement is much lower in eastern Germany (see Jung andSchnabel 2011, Ellguth andKohaut 2014). Interestingly, Jung and Schnabel (2011) find that whereas their economic model does a good job in explaining the probability of paying higher wages than collectively agreed in western Germany, the explanatory factors identified are of much lower relevance in eastern Germany.…”
Section: Wage Setting and Industrial Relationsmentioning
confidence: 98%
“…In a recent analysis covering the time period 1996 to 2010 and based on the IAB Establishment Panel, Jung (2014) shows that firms' employment adjustment process is somewhat faster (so that adjustment costs are lower) in eastern than in western Germany, but the difference is not statistically significant. This confirms the findings of previous studies by Bellmann and Pahnke (2006) and Fuchs (2010).…”
Section: Labour Demandmentioning
confidence: 98%
“…However, this response does not imply that respondents necessarily find this a problem or prefer to be able to fire workers with "ease." High-performing companies seldom sack their greatest asset-their highly trained staff-even where they can, as research in Germany indicates: After new German laws made firing somewhat easier, employment turnover actually decreased between 1996 and 2010 (Jung 2014).…”
Section: Major Flaw #2: Token "Inclusion" Of Environmental and Social Indicatorsmentioning
confidence: 99%